2021
DOI: 10.1136/thoraxjnl-2020-215745
|View full text |Cite
|
Sign up to set email alerts
|

Blocking LOXL2 and TGFβ1 signalling induces collagen I turnover in precision-cut lung slices derived from patients with idiopathic pulmonary fibrosis

Abstract: We recently identified epigallocatechin gallate (EGCG), a trihydroxyphenolic compound, as a dual inhibitor of lysyl oxidase-like2 and transforming growth factor-β1 (TGFβ1) receptor kinase that when given orally to patients with idiopathic pulmonary fibrosis (IPF) reversed profibrotic biomarkers in their diagnostic biopsies. Here, we extend these findings to advanced pulmonary fibrosis using cultured precision-cut lung slices from explants of patients with IPF undergoing transplantation. During these experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…Notably, SOX9 regulates the expression of LOXL2 an important ECM organizing enzyme that plays a crucial role in matrix remodeling and fibrogenesis (28). Previous studies have demonstrated that LOXL2 is a marker for IPF progression, and its inhibition resulted in the slower progression of the disease (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, SOX9 regulates the expression of LOXL2 an important ECM organizing enzyme that plays a crucial role in matrix remodeling and fibrogenesis (28). Previous studies have demonstrated that LOXL2 is a marker for IPF progression, and its inhibition resulted in the slower progression of the disease (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, SOX9 regulates the expression of LOXL2, an important ECM-organizing enzyme that plays a crucial role in matrix remodeling and fibrogenesis ( 27 ). Previous studies have demonstrated that LOXL2 is a marker for IPF progression, and its inhibition resulted in the slower progression of the disease ( 27 29 ). SOX9 is well recognized as a transcriptional regulator for various ECM-related genes based on studies related to chondrogenesis and cancer cell types ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the nuclear localization of LOXL2 protein has been associated with the progression of lung fibrosis [ 45 ] and suggests a dynamic regulatory role ( Table 1 ). In this regard, inhibition of LOXL2 in ex vivo lung explants from patients with IPF was shown to induce collagen turnover [ 46 ] ( Table 1 ). LOXL1 and LOXL3 have also been identified in the pathogenesis of IPF [ 41 , 43 , 47 ] ( Table 1 ).…”
Section: Altered Expression Of Lysyl Oxidases In Non-cancerous Settingsmentioning
confidence: 99%
“…Both pirfenidone and nintedanib have recently been shown to have an effect on epithelial-cell phenotypes when evaluated in an ex vivo precision-cut lung slice (PCLS) model with induction of early fibrotic remodeling via a cocktail of growth factors ( 152 , 153 ); however, how similar this injury model is to IPF is not yet known. Alternatively, other work has evaluated potential compounds in explanted IPF tissue, representing end-stage disease ( 154 , 155 ). How relevant either the PCLS approach or even the use of TGF-β stimulation alone on PCLSs might be in predicting clinical efficacy remains unknown.…”
Section: Repairing the Damaged Lung Epithelium: The Future Of Ipf Therapeutics?mentioning
confidence: 99%